Plant aphid interactions : effects of diuraphis noxia and rhopalosiphum padi on the structure and function of the transport systems of leaves of wheat and barley - Saheed, Sefiu Adekilekun (Rhodes University, Faculty of Science, Botany Department, 2008)
The infestation of the cultivated grain crops by phloem feeding aphids has generated a great deal of interest over the years, due to the serious damage they cause to the crops and yield losses that result. The mechanism of the interaction between aphids and host plants remains largely unknown in spite of efforts to understand the basis of aphid feeding on grain crops. Greater efforts are required to explain the mechanism(s) of this interaction in order to achieve sustainable agriculture. This thesis focused on an investigation of the mechanism of feeding by the Russian wheat aphid, Diuraphis noxia Mordvilko (RWA) and the bird cherry-oat aphid, Rhopalosiphum padi L. (BCA) on barley and wheat cultivars. These two aphids co-occur naturally, but they inflict very different feeding effects on host plants. Structural and functional approaches were employed to investigate their feeding habits and these were then related to the observed differences in their host plants. Transmission electron microscopy (TEM) techniques were used to study the ultrastructural damage, while fluorescence microscopy techniques "“ using aniline blue fluorochrome (a specific stain for callose) and 5, 6-CFDA (a phloem-mobile fluorophore) "“ were employed to investigate the functional response to damage via wound callose formation and phloem transport capacity respectively. RT-PCR and quantitative real-time RT-PCR techniques were used to investigate the regulation of the genes involved in callose synthesis and degradation at the transcriptional level. Morphological observation of the damage caused by the aphids show that infestation by RWA results in extensive leaf chlorosis, necrosis and rolling, while infestation by BCA does not lead to any observable symptoms within the same period. Interestingly, the population study shows that BCA breeds faster than RWA within the two-week experimental period. The ultrastructural study of feeding damage caused by the two aphids on the vascular bundles of susceptible barley cv Clipper, shows a different patterns of damage. Probing the vascular bundles results in the puncturing of vascular parenchyma by both aphids, but severe damage occurs in sieve tubes-companion cell complex during sustained feeding by RWA. In contrast, less damage occurs when BCA feeds on the phloem. Drinking from the xylem by RWA results in deposition of a large quantity of electron-dense watery saliva, which apparently seals the xylem vessels completely, by blocking all the pit membrane fields between the xylem vessels and associated parenchyma cells. In contrast, drinking from xylem by BCA results in deposition of a dense, granular saliva into the xylem vessels only, which does not appear to totally occlude the pit membrane fields. This is the first known report in which ultrastructural evidence of aphids' drinking in xylem is provided. The comparative effects of RWA feeding on a susceptible Betta and resistant Betta-Dn1 wheat cultivars showed that after two weeks, the Betta cultivar expressed damage symptoms such as chlorosis, necrosis and leaf roll, while few chlorotic patches and necrotic spots occur in resistant Betta-Dn1 cultivars. An ultrastructural investigation of the feeding damage caused to all leaf tissues revealed, for the first time, that RWA is capable of both intra- and inter-cellular probing within mesophyll cells. Probing in the mesophyll cells induces a more severe damage in susceptible Betta than in the resistant Betta-Dn1 counterpart. Similar differences in damage occurred during feeding in the thin-walled sieve tubes of the phloem, with the sieve tubes of the Betta showing more damage than that of the resistant Betta-Dn1. However, drinking from xylem resulted in the characteristic occlusion of metaxylem vessels by copious deposition of saliva by RWA in both Betta and Betta-Dn1 cultivars. In all cases of probing, feeding, and drinking by RWA in both cultivars, all probed cells with evidence of salivary material deposit and those cells adjacent to salivary material deposit, exhibit significant damage in susceptible Betta cultivar, whereas similar cells in Betta-Dn1 cultivars do not show as damage as severe. Investigation of the functional response of the plants to feeding by aphids through the deposition of wound-induced callose shows that formation and deposition of wound callose occurs in both longitudinal and cross veins within 24h of feeding by RWA. This deposition increases through short-term feeding (72h) and prolonged feeding (14d). This is in sharp contrast to the observations with BCA feeding,where little or no callose formation occurs within the same time frame. Callose formation and deposition occurs only when a higher population of BCA feeds on barley leaves. This is the first report of aphid-induced wound callose by BCA. In all cases of callose deposition, aphid stylet tracks were associated with callose and the deposition of callose appears to be a permanent feature, because wound callose remained in the leaf tissues even after 120h of the aphids' removal. Wound callose signals (defence and anti-defence) are discovered to be transported in the phloem tissues and are dependent on the direction of assimilate flow. Examination of the possible regulation of wound callose genes at the transcriptional level shows that the two expressed glucan synthase gene sequences (GSL "“ genes involved in callose formation) analysed did not show any significant increase or regulation upon aphid infestation. Contrary to expectation, all three aphid-induced Î²-1, 3-glucanases (genes which are thought to be involved in callose degradation) showed higher expression in RWA-infested tissue than in BCA-infested tissue. The results of the feeding damage on the transport capacity of the phloem shows that BCA infestation does not lead to a significant reduction in the phloem transport capacity during short-term feeding (72h), while RWA-infested leaves showed considerable reduction in the transport capacity of the phloem within the same period. However, prolonged feeding (14d) by BCA induces a considerable reduction on the transport capacity of the phloem on the infested tissues. In contrast, a marked reduction in the transport capacity of the phloem occurs in RWA-infested leaves and in most cases, complete cessation of transport ensues. In conclusion, these data collectively suggest that RWA is a serious and most destructive phloem feeder in comparison to the BCA. RWA causes severe damage to all cellular tissues of the host plants, which result in apoplasmic and symplasmic isolation of xylem and phloem tissues, while BCA infestation does not result in such isolation within the same time and population levels. Resistance genes appear to function by conferring resistance to cell damage on the resistant cultivars during aphid feeding. Responses by plants to aphid infestation via wound callose deposition are again shown to be species-specific. A quick response results when RWA feeds, even at a very low population level, while a response occurs only at a higher infestation level by BCA, and this response was shown as not regulated at the transcriptional level. Differences in the damage to leaf tissues and wound callose deposition eventually lead to varying degrees of damage to the transport capacity of the phloem. These differences in the damage signatures are hereby suggested to be the cause of the diversity in the observed damage symptoms and the yield losses upon infestation by the two aphid species.
Keywords: Russian wheat aphid; Rhopalosiphum padi; Aphids -- Host plants; Wheat -- Diseases and pests